Liberación de fluoruros de materiales utilizados como selladores (un estudio in vitro) - Urquía-M., María del Carmen; Brasca, Nora; Ríos, María Alejandra; Girardi, Mónica; Joekes, Silvia (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This in-vitro study evaluated the degree of fluoride release from different alternative materials used as pit and fissure sealants during different time periods. Two resin-based sealants, a flowable composite resin, two compomers and two conventional GICs were used. Disk-shaped (specimens) were prepared and immersed in 50mL of distilled water to which 50 mL of a buffer solution was added. A fluoride ion detector was employed to determine fluoride concentrations during different periods of time after immersion. Material and time factors had a significant influence on results (p < 0,0001). Composite resins showed the least fluoride release in comparison to the remaining experimental materials. It can be concluded that the degree of fluoride release varies according to time and the particular features of each material.